Neuromarketing Exploring the Brain of the Consumer - Zurawicki, Leon.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Over the last 10 years advances in the new field of neuromarketing have yielded a host of findings which defy common stereotypes about consumer behavior. Reason and emotions do not necessarily appear as opposing forces. Rather, they complement one another. Hence, it reveals that consumers utilize mental accounting processes different from those assumed in marketers' logical inferences when it comes to time, problems with rating and choosing, and in post-purchase evaluation. People are often guided by illusions not only when they perceive the outside world but also when planning their actions - and consumer behavior is no exception. Strengthening the control over their own desires and the ability to navigate the maze of data are crucial skills consumers can gain to benefit themselves, marketers and the public. Understanding the mind of the consumer is the hardest task faced by business researchers. This book presents the first analytical perspective on the brain - and biometric studies which open a new frontier in market research.
Exploring the Brain -- Consumption as Feelings -- Neural Underpinnings of Risk Handling, Developing Preference and Choosing -- Neural Bases for Segmentation and Positioning -- Applying Neuroscience and Biometrics to the Practice of Marketing.
Keywords: Economics; Neurobiology; Marketing; Economics/Management Science; Marketing; Neurobiology